THE MADURA FOOT - A CASE REPORT - Nazimuddin Mohammad; Chowdhury Arif; Parvin Rukhsana; Uddin Rokon; Razzak Abdur; Hoque Moydul (Our Dermatology Online, 2011)
Madura foot or mycetoma is a chronic granulomatous disease characterized by localized infection of subcutaneous tissues by actinomycetes or fungi. The inflammatory response can extend to the underlying bone. Mycetoma was described first in the mid 1800s and was initially called Madura foot. The infection can be caused by true fungi (eumycetoma) in 40%, or filamentous bacteria (actinomycetoma) in 60%.Actinomycetoma may be due to Actinomadura madurae, Actinomadura pelletieri, Streptomyces somaliensis, Nocardia species. The infection, which may remain latent for a time, forms small, subcutaneous swellings that enlarge, soften with pus, and break through the skin surface, with concurrent invasion of deeper tissues. Sulfonamide, iodide, and antibiotic therapy have been used against actinomycotic infections, but the fungi are more resistant to treatment. We reported a patient of madura foot from International Medical College Hospital, Tongi, Gazipur. A 82-years old male was admitted to the International medical college hospital with a 16 months history of swelling with multiple discharging sinuses filled with granules localized in his right foot. Pus was examined by gram staining and periodic acid Schiff (PAS) staining. Moderate number of filamentous branching gram positive bacilli were found . The organism was recognized as a member of the actinomyces genus. PAS staining did not reveal any other organism. The aggressive course and progression of the disease affected the short bones of the involved foot. The patient was diagnosed as a case of Madura foot and was treated in the same hospital.